GLOOTT model : a pedagogically-enriched design framework of learning environment to improve higher order thinking skills - Wee, Chuen Tan; Aris, Baharuddin; Abu, Mohd. Salleh (2006)
Learning object design currently leads the instructional technologist towards more effective instructional design, development and delivery of learning content. There is a considerable amount of literature discussing about the potential use of learning object in e-learning. However, most of the works were mainly focused on the standard forms of metadata and technical-related issues leaving behind the importance of pedagogical factors. This paper comprises two parts. In the first part, the authors examine the attributes of learning objects in providing a customized, individualized and flexible learning environment with an approach that is grounded in generative learning principles of learner-centered and learner-controlled learning environment. The cognitive and pedagogical relationships between generative learning and higher order thinking skills (HOTs) are briefly reviewed. The second part proposes a design and development framework of Generative Learning Object Organizer and Thinking Task (or simply called GLOOTT), a pedagogically-enriched web-based learning environment designed to improve HOTs.